Investigation of Hardness and Impact Test in Silane Treated Silicon Added Kenaf Hybrid Composite Material - et. al., N. Parthipan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now a days the natural composite used in various commercial application. Dealing with conditions is one of the factors that out and out impacts the properties and attributes of the polymer cross section composites things. In this way, the nano silica reinforced natural composite materials dealing with mastermind to give up the ideal properties of the composite things. In this work, biodegradable composites from unidirectional long kenaf fiber were produced by hot crushing methodology. The examination of progress was used to upgrade just as choose the impacting the malleable quality. The test was conducted in mixing of hot pressing boundaries technology, finally were found that high impact and hardness value of hybrid silicon treated composite materials.